Grape Seed Proanthocyanidins Modulate the Hepatic Molecular Clock via MicroRNAs. Issue 23 (26th October 2022) - Manocchio, Francesca; Soliz‐Rueda, Jorge R.; Ribas‐Latre, Aleix; Bravo, Francisca Isabel; Arola‐Arnal, Anna; Suarez, Manuel; Muguerza, Begoña
Abstract : Scope: Circadian rhythm is an endogenous and self‐sustained timing system, responsible for the coordination of daily processes in 24‐h timescale. It is regulated by an endogenous molecular clock, which is sensitive to external cues as light and food. This study has previously shown that grape seed proanthocyanidins extract (GSPE) regulates the hepatic molecular clock. Moreover, GSPE is known to interact with some microRNAs (miRNAs). Therefore, the aim of this study is to evaluate if the activity of GSPE as modulator of hepatic clock genes can be mediated by miRNAs. Methods and results: 250 mg kg −1 of GSPE is administered to Wistar rats before a 6‐h jet lag and sacrificed at different time points. GSPE modulated both expression of Bmal1 and miR‐27b‐3p in the liver. Cosinor‐based analysis reveals that both Bmal1 and miR‐27b‐3p expression follow a circadian rhythm, a negative interaction between them, and the role of GSPE adjusting the hepatic peripheral clock via miRNA. Additionally, in vitro studies show that Bmal1 is sensitive to GSPE (25 mg L −1 ). However, this effect is independent of miR‐27b‐3p. Conclusion: miRNA regulation of peripheral clocks via GSPE may be part of a complex mechanism that involves the crosstalk with the central system rather than a direct effect. Abstract : Jet‐lagged rats and HepG2 cells were used to evaluate if the activity of grape seed proanthocyanidins extract (GSPE) as modulator of hepatic clock genes is mediated by miRNAs. GSPE modulates expression of hepatic Bmal1 and miR‐27b‐3p. Moreover, cosinor‐based analysis reveals that both Bmal1 and miR‐27b‐3p expression follow a circadian rhythm and that GSPE adjusted the hepatic peripheral clock via miRNA.